Perceived effectiveness of creative new product development in virtual teams - Kline, Miro (Teorija in praksa, 2011)
Virtual teams are arising as a new trend in New Product Development (NPD). They are perceived to be highly creative in reaching suitable new product solutions, as they are not limited by local resources, organizational boundaries and climate. In this paper we study how students involved in NPD in virtual environments perceive their creative effort and final NPD result - development of a functioning prototype. We approach and study the presented issue on a 2011 generation of Engineering and Design students involved in a design course entitled European Global Product Realization. This project has been developed by 5 European Universities to enable students to gain practical experience in virtual product development. The results show that the students do not perceive working in virtual environments as relevant for creativity. On the other hand, however, working in virtual teams induces effectiveness of creative new product development, directly, as well as indirectly through the structure of the design process. Similarly, the students also perceive creativity to have a positive effect on the design process, as well as on the final NPD result. The results only partially support the notion that virtual teams are highly creative in NDP.
Keywords: Creativity; Ustvarjalnost; New products; Novi izdelki; Virtual work teams; Navidezne delovne skupine; izdelki; proizvodi; razvoj; skupinsko delo